Nostalgia Marketing: A Systematic Literature Review Using the Research Onion Framework - Benni Ahdiyana Pamungkas; Cristian Hadi Pranata (Jurnal Multidisiplin Indonesia, 2026)
This study aims to identify future research directions and opportunities in nostalgia marketing through the Systematic Literature Review (SLR) using the Research Onion framework. A total of 22 Scopus-indexed articles were screened following PRISMA guidelines, of which 11 articles were selected for in-depth analysis based on research philosophy, approaches, methods, strategies, time horizons, and data analysis techniques. The findings indicate that nostalgia marketing is grounded in two paradigms, interpretivism and positivism, with a relatively balanced use of inductive and deductive approaches. They employ qualitative, quantitative, and mixed-method designs, utilizing diverse strategies such as literature reviews, case studies, surveys, and experiments. Cross-sectional designs are found to be the most commonly adopted time horizon. This study provides a comprehensive overview of the methodological landscape of nostalgia marketing and highlights key directions for future inquiry. The findings offer valuable implications for both researchers and practitioners by demonstrating how nostalgia-driven strategies can be effectively leveraged across industries. Furthermore, this study lays an initial foundation for the development of theoretical models of nostalgia marketing, particularly in the Indonesian context.